Well-Come Back! Professional Basketball Players Perceptions of Psychosocial and Behavioral Factors Influencing a Return to Pre-injury Levels - Conti, Cristiana; di Fronso, Selenia; Pivetti, Monica; Robazza, Claudio; Podlog, Leslie; Bertollo, Maurizio (Frontiers in Psychology, 2019)
The psychological factors influencing a return to sport has gained increased research attention. In the current investigation, we explored professional basketball players’ perceptions of the psychological factors facilitating a return to performance equal to or exceeding previous performance standards. We also sought to describe athletes’ experiences – both positive and negative – of returning to sport following injury recovery. Ten Italian professional male basketball players (age range 22-36 years), were retrospectively interviewed in relation to three time-periods: (1) from the commencement of rehabilitation to their first official competition, (2) the first official competition, and (3) the six-months following the initial competition. Hierarchical content analysis of the data revealed numerous themes across the three time periods. In regards to Period 1, participants indicated that social support, investment in rehabilitation and training programs, coping skills and motivation were fundamental in reaching pre-injury performance levels. During their first official game (i.e. Period 2), athletes reported that realistic performance expectations, focusing on the performance, positive emotions, motivation, arousal and social support facilitated their return to sport. Athletes however, also described a predominance of factors that hindered their return to pre- injury levels (i.e., low confidence in personal abilities, decrements in skill execution and dysfunctional physical sensations). Moreover, participants typically described a substandard level of performance during their first competition back following injury. In recounting experiences during the six months following their first official game, basketballers reported improvements in skill execution and highlighted the importance of coping skills, motivation and social support. The process of restoring self-confidence in one’s ability to successfully perform was perceived as crucial in enabling participants to move beyond a mere return to sport to a return to high performance ─ that is, to reach a level of proficiency equal to or exceeding previous performance standards. Findings support the relevance of cognitive, emotional and behavioral responses highlighted in the Integrated Model and suggest the importance of addressing psychological factors throughout the return-to-sport process. Finally, results from the present study hold a number of practical implications for athletes’ aiming to achieve a return to pre-injury levels.